Design of Hybrid Renewable Energy Systems for a Village in Selangor, Malaysia - Muaz Izzuddeen Sabudin; Mohd Noor Syawal Mustapha; Muhammad Adzim Mohd Rozi; Devaraj Tharuma Rajah (Malaysian Journal of Science and Advanced Technology, 2021)
Conventional fossil fuel generation releases high amount of carbon dioxide and contributed to the climate change problem. Hence, the use of renewable energy sources is important to mitigate the greenhouse gasses emissions. Remote or rural areas relies heavily on diesel generations for electricity due to no grid connection. Therefore, a microgrid system with renewable resources has high potential for implementation in these areas.  This paper discusses on the hybrid renewable energy system design for a village in Selangor, Malaysia. The load profile data collected based on survey and interview with the locals. Meanwhile, the solar radiation and temperature data were obtained from NASA POWER database. The hydropower resource data was obtained through site visit at the location. HOMER software was used to simulate and determine the most optimal hybrid renewable energy system. Additionally, sensitivity analysis was conducted to identify effect of growth in load profile with respect to the optimal configuration. The optimization results shows that PV-hydro-grid is the most optimal system. It has lower Net Present Cost with higher renewable penetration compared to other configurations.